MEDICINAL PROPERTIES OF BALA (SIDA CORDIFOLIA LINN. AND ITS SPECIES) - Kumar Sharma, Ashwini (International Journal of Ayurveda and Pharma Research, 2015)
The Indian system of medicine, Ayurveda, medical science practiced for a long time for disease free life. It relies mainly upon the medicinal plants (herbs) for the management of various ailments/diseases. Bala (Sida cordifolia Linn.) that is also known as Indian Ephedra is a plant drug, which is used in the various medicines in Ayurveda, Unani and Siddha system of medicine since ages. It has good medicinal value and useful to treat diseases like fever, weight loss, asthma, chronic bowel complaints and nervous system disease and acts as analgesic, anti-inflammatory, hypoglycemic activities etc. Bala is described as Rasayan, Vishaghana, Balya and Pramehaghna in the Vedic literature. Caraka described Bala under Balya, Brumhani dashaimani, while Susruta described both Bala and Atibala in Madhur skandha. It is extensively used for Ayurvedic therapeutics internally as well as externally. The root of the herb is used as a good tonic and immunomodulator. Atibala is in Atharva Parisista along with Bala and other drugs. Caraka described it among the Balya group of drugs whereas Carakapani considered it as Pitbala. Atibala is quoted in the Nighantus in the context of Bala catustaya. Nagbala or Gangaruki are not found in vedic literature. Nagbala term is used by Brhat trayi repeatedly whereas Gangeruki which is synonym of Nagbala is mentioned thrice only. The present review explained on the sida species and the traditional uses, Ayurvedic preparation and pharmacological properties.